The Relationship Between Self-efficacy and Intention to Engage in Premarital Sex Among Adolescent Students in Public Secondary Schools in Tanzania - Rushahu, Bernadetha; Mbawala, Joseph (Tanzania Journal for Population studies and Development, 2023)
The study examined the relationship between self-efficacy and intention to engage in pre-marital sex among adolescent students in public secondary schools in Tanzania. It employed a quantitative approach guided by correlation design, using structured questionnaires. Three hundred and fifty-seven (357) participants were involved: 172 males and 185 females. The results showed that 61.6% of the respondents had a reasonably high level of self-efficacy, while 70.1% had a lower level of intention to engage in premarital sex. It was also found that there was no statistical relationship between self-efficacy and intention to engage in premarital sex among adolescent students in public secondary schools (p=0.78>0.05). Therefore, the government—through the Ministry of Education, Science and Technology—should introduce self-efficacy programmes in the secondary school curriculum, which will help improve moral, social, cognitive and emotional qualities in adolescent students, so that they abstain from any risky sexual behaviours.